Living the good life with Helen and Scott Nearing - Hoskyns-Abrahall, John (Oley, PA : Bullfrog Films, 1997)
Shows that homesteading is not only viable in modern America, but beneficial to the individuals and society as well. Views Helen and Scott Nearing, who 45 years ago quit city life and went back to the land, growing their own food, building their own house, but still pursuing their professional interests
Copy in DVD Format
Photographer, Robert Elfstrom
Narrated by David Naughton
VHS Format
Keywords: Nearing, Helen; Nearing, Scott, -- 1883-1983; Country life; Socialists -- United States -- Biography